Cerebral Oxygenation and Autoregulation in Very Preterm Infants Developing IVH During the Transitional Period: A Pilot Study - Cimatti, Anna Giulia; Martini, Silvia; Galletti, Silvia; Vitali, Francesca; Aceti, Arianna; Frabboni, Giulia; Faldella, Giacomo; Corvaglia, Luigi (Frontiers in Pediatrics, 2020)
Background: The transitional period, defined as the first 72 h after preterm birth, is often characterized by a significant hemodynamic instability, which represents an important risk factor for such neurological complications of prematurity as intraventricular hemorrhage (IVH). The impairment of cerebral autoregulation plays a key role in the pathogenesis of IVH, whose incidence is highest during the transitional period. This pilot study aimed to evaluate whether patterns of cerebral autoregulation and oxygenation differ in relation to IVH development in very preterm infants during the transitional period. Methods: Infants <32 weeks' gestation were enrolled within 12 h from birth. A simultaneous monitoring of cerebral oxygenation (CrSO2) by near-infrared spectroscopy and of heart rate and peripheral oxygen saturation by pulse oximetry was performed over the first 72 h. Cerebral fractional oxygen extraction (cFTOE) and tissue oxygenation-heart rate reactivity index (TOHRx), which represents a marker of cerebrovascular reactivity, were calculated. Daily cranial and cardiac ultrasound scans were performed, in order to assess the hemodynamic status and to detect a possible IVH onset. CrSO2 and cFTOE, clustered on 6-hour epochs, were compared between infants who developed IVH during the study period and those who did not. A between-group comparison of TOHRx before and after IVH detection was also performed. Results: Twenty preterm infants with a median gestational age of 27 weeks (interquartile range, IQR: 25-30 weeks) and median birth weight of 895 g (IQR: 822-1208 g) were enrolled. Of these, 8 developed IVH. The median age at IVH detection was 40 h (IQR: 30-48 h). Pre-IVH TOHRx was significantly higher compared to matched control periods (p <0.001). CrSO2 was significantly lower from 12 to 30 h and from 42 h onwards in cases compared to controls; however, a temporary CrSO2 rise preceded IVH detection. Similarly, cFTOE was significantly higher in IVH infants from 12 to 30 h and from 48 to 72 h, with a transient decrease between the two periods. Conclusions: In preterm infants during the transitional period, the development of IVH is preceded by transient changes in cerebral oxygenation and oxygen extraction which, in turn, may underlie an early impairment of cerebral autoregulation. Larger studies are needed to confirm these preliminary findings.